Morphological and Molecular Variability in Alternaria burnsii and Alternaria alternata Causing Blight Disease of Cummin (Cuminum cyminum L.) - Singh, Surendra; Bairwa, Shri Kishan; Trivedi, Amit; Meena, Rajesh Kumar; Meena, S. C.; Prasad, Dasharath (International Journal of Bio-resource and Stress Management, 2016)
burnsiiand A. alternatashowed considerable variations in growth pattern, colony diameter, rate of sporulation and in conidial morphology. Among the isolates of A. burnsii maximum colony diameter was observed in UDPAb-1 and least in JSL Ab-3 while in A. alternata maximum colony diameter was observed in isolate JLR Aa-2 and least in JSL Aa-3 after 7 days of incubation. Maximum number of spores (15.2×103 conidia mm-2) was produced by isolate UDP Ab-1 in A. burnsii and among A. alternata it was maximum in isolate JLR Aa-2 and least (9.2×103 conidia mm-2) by JSL Aa-3. Largest conidial size 88-111×26-32 µm (with beak) and 30-38×14-18 µm (without beak) was observed in isolates UDP Ab-1 among isolates of A. burnsii and smallest conidial size 70-88×25-32 µm (with beak) and 31-39×15-19 µm (without beak) was observed in isolate JLR Ab-1.Whereas, among A. alternata isolates, largest conidial size 38-48×9-11 µm (with beak) and 30-38×11-14 µm (without beak) was observed in isolates JSL Aa-2. Further, molecular variability was assessed using nine RAPD primers and all these 9 primers showed polymorphism. Primers OPB-20, OPC-2 and OPG-17 generated maximum 10 bands with PIC value of 0.31, 0.34 and 0.33 respectively. A total number of 76 amplified bands were obtained and out of them 41 were polymorphic. The maximum and minimum percentage of polymorphism is observed in primers OPC-2 (80%) and OPA-19 (25%) respectively, these results exhibits the importance of RAPD markers for diversity analysis.